Outcomes and risk factors for cancer patients undergoing endoscopic intervention of malignant biliary obstruction - Haag, Georg Martin; Herrmann, Thomas; Jäger, Dirk; Stremmel, Wolfgang; Schemmer, Peter; Sauer, Peter; Gotthardt, Daniel (BMC gastroenterology, 2015)
Malignant bile duct obstruction is a common problem among cancer patients with hepatic or lymphatic metastases. Endoscopic retrograde cholangiography (ERC) with the placement of a stent is the method of choice to improve biliary flow. Only little data exist concerning the outcome of patients with malignant biliary obstruction in relationship to microbial isolates from bile.
Gesehen am 18.02.2021